2016
DOI: 10.1002/acn3.327
|View full text |Cite
|
Sign up to set email alerts
|

Tumor prevention facilitates delayed transplant of stem cell‐derived motoneurons

Abstract: ObjectiveNerve injuries resulting in prolonged periods of denervation result in poor recovery of motor function. We have previously shown that embryonic stem cell‐derived motoneurons transplanted at the time of transection into a peripheral nerve can functionally reinnervate muscle. For clinical relevance, we now focused on delaying transplantation to assess reinnervation after prolonged denervation.MethodsEmbryonic stem cell‐derived motoneurons were transplanted into the distal segments of transected tibial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, we investigated the T-cell receptor-β (TCR-β) targeting monoclonal antibody, mAb H57-597, which has previously been shown to effectively promote long-term heart allograft survival in mice ( Miyahara et al, 2012 ). In addition, since our findings indicated that immunosuppression results in a greater risk of tumour formation from carry-over pluripotent stem cells, differentiated ChR2 + motor neurons were also pre-treated with mitomycin-C (MMC; 2 μg/ml for 2 hr) prior to engraftment, to eliminate tumorigenic cells ( Magown et al, 2016 ), to further enhance the translational potential. MMC-treated ChR2 + motor neurons were unilaterally engrafted into the tibial nerve of symptomatic SOD1 G93A mice (aged 95.7±4.6 days) in conjunction with transient H57-597 mAb delivery (1 mg, kg-1; i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we investigated the T-cell receptor-β (TCR-β) targeting monoclonal antibody, mAb H57-597, which has previously been shown to effectively promote long-term heart allograft survival in mice ( Miyahara et al, 2012 ). In addition, since our findings indicated that immunosuppression results in a greater risk of tumour formation from carry-over pluripotent stem cells, differentiated ChR2 + motor neurons were also pre-treated with mitomycin-C (MMC; 2 μg/ml for 2 hr) prior to engraftment, to eliminate tumorigenic cells ( Magown et al, 2016 ), to further enhance the translational potential. MMC-treated ChR2 + motor neurons were unilaterally engrafted into the tibial nerve of symptomatic SOD1 G93A mice (aged 95.7±4.6 days) in conjunction with transient H57-597 mAb delivery (1 mg, kg-1; i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we investigated the T-cell receptor-β (TCR-β) targeting monoclonal antibody, mAb H57-597, which has previously been shown to effectively promote long-term heart allograft survival in mice 28 . In addition, since our ndings indicated that immunosuppression results in a greater risk of tumour formation from carry-over pluripotent stem cells, differentiated ChR2 + motor neurons were also pretreated with mitomycin-C (MMC; 2 μg/ml for 2 hrs) prior to engraftment, to eliminate tumorigenic cells 29 , to further enhance the translational potential. MMC-treated ChR2 + motor neurons were unilaterally engrafted into the tibial nerve of symptomatic SOD1 G93A mice (aged 95.7 ±4.6 days) in conjunction with transient H57-597 mAb delivery (1μg, kg -1 ; i.p.…”
Section: T-cell Modulatory Immunosuppression Confers Graft Survival A...mentioning
confidence: 99%
“…However, despite the promise of hiPSCs derived cells to treat disease, tumorigenicity of residual pluripotent-like cells in differentiated stem cells remains a concern [24,25]. At present, numerous techniques have been applied to remove teratoma-forming potential from hiPSC-derived products, such as pretreatment with antimitotic agents and delayed transplant [26], sorting with flourescent activated cell sorting (FACS) [27], magnetic activated cell sorting (MACS) [28], introduction of inducible suicide genes [29], and complete differentiation into mature dopaminergic neurons [30]. Unfortunately, each of these methods have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with antimitotic agents and delayed transplant or complete differentiation into mature dopaminergic neurons increases turn-around time to derive therapeutic cells, and could make it difficult to transplant cells during the short optimal timing of transplantation in the subacute phase [31]. Although inducible suicide genes respond in 95% of cells , they are unlikely to eliminate teratoma because as few as 2 embryonic stem cells in two million non-neoplastic cells are capable of forming tumors in 60% of the transplants [26,29]. Additionally, FACS and MACS have thus far proven insufficient to eliminate teratoma-forming potential and both require pre-labeling cells with antibodies, which could interfere with proliferation and differentiation [27,28].…”
Section: Introductionmentioning
confidence: 99%